Silhaṭ meṉ Urdū - Bismil, Muḥammad ʻAbduljalīl (Silsilah-yi ma̤tbūʻāt-i Anjuman Taraqqī-yi Urdū Pākistān ;, 1981)
Biographical sketches of noted Urdu poets and litterateurs of Sylhet, Bangladesh from the 14th century to 1967; includes samples of their works.